A review on optoelectronic device applications of 2D transition metal carbides and nitrides. (15th February 2021) - Zhang, Xiwei; Shao, Jiahua; Yan, Chenxi; Qin, Ruijie; Lu, Zhihui; Geng, Huijuan; Xu, Tongshui; Ju, Lin
Abstract: As a new branch of two-dimensional materials, MXenes are considered to have distinguished and controllable optical and electronic properties. Consequently, MXenes could play important roles in optoelectronic device applications, such as: transparent conductive electrode, conducting additives, and charge transfer layers. In this review, we summarized the unique optical and electronic properties of MXenes as well as recent advances in their optoelectronic device applications. Firstly, the excellent and adjustable optical and electronic properties of MXenes are introduced. Secondly, recent progress in optoelectronic device applications of MXenes, such as: photodetectors, photovoltaic devices, light emitting diodes, are summarized. Finally, some major challenges and opportunities towards the practical optoelectronic device applications of MXenes, which need be further investigated, have been discussed. We hope our work could guide the following development and research of MXenes-based optoelectronic devices. Graphical abstract: Unlabelled Image Highlights: Advantages in optical and electronic properties of MXenes are described. Recent progresses in the use of MXenes in optoelectronic devices are summarized. The opportunities and practical challenges for optoelectronic device application and design of MXenes are explored.